The Effect of Implementing Marketing Mix Strategy on Increasing the Number of Outpatients at Gunung Tua Regional Hospital North Padang Lawas - Pohan, Tiasa; Nasution, Wardani; Saputra, Johan (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
This study observes the effect of implementing marketing strategies using marketing mix on increasing the number of outpatients. The purpose of this study was to determine the effect of marketing mix on increasing the number of patients and to determine which variables in the marketing mix have a direct effect on increasing the number of outpatients at RSUD Gunung Tua Hospital. This study is a non-experimental study with a purposive/purposive sampling approach. The number of samples in this study was 50 people and sampling was carried out by purposive/purposive sampling. The data were analyzed using the validity and reliability test method for each questionnaire item, multiple regression analysis, t-test, and F-test. From the questionnaire test, the results of each question item were valid and reliable, and by using multiple regression analysis through t-test and F-test, the results of significance <0.05 were obtained. This shows that partially or simultaneously all independent variables have an effect on the dependent variable, meaning that the effect of implementing strategies using Marketing Mix has an effect on increasing the number of outpatients. Based on multiple regression analysis, it is known that there is an influence of the implementation of the strategy using Marketing Mix on the increase in the number of outpatients, so that it is possible to improve the quality of patient health services, in the outpatient unit of RSUD Gunung Tua Padang Lawas Utara. The conclusion of this study is that simultaneously or together it shows that the implementation of the concept with Marketing Mix consisting of products, prices, places and promotions together on the increase in the number of outpatients at RSUD Gunung Tua Padang Lawas Utara Hospital. Based on partial testing, the Product Variable has an influence on the increase in the number of patients.